The daughters take the stage - Philbin, Joanna (The Daughters, 2011)
Fourteen-year-old Hudson is a gifted singer/songwriter like her mother, pop sensation Holla Jones, but while working on her debut album, Hudson struggles to convince her mother that she would rather stick with her own intimate style than follow her mother's path to fame.